Business plan for grabahome - Mrksa, Mario (2021)
The main purpose of this work project is to simulate a real-life scenario of „pitching“ grabAhome, which was founded in January 2021, to potential investors. The business plan explains the current problem for the midterm rental market in Southeast Europe, Malta and Cyprus, and reveals that the solution to the problem is a digital marketplace for midterm rental in Southeast Europe.